Photon Contamination Analysis (Bremsstrahlung tail) of Electron Beams in Small Fields - Barua, Sadip; Hasnat, M A; Alim, Samiul; Zohra, Fatema Tuz; Poddar, Priyanka; Islam, M Rafiqul; Sarma, S C B; Purohit, Santunu; Hoque, Mohammad Nasirul; Ahasan, M M (Bangladesh Journal of Nuclear Medicine, 2025)
Intensity-modulated radiotherapy, volumetric arc radiotherapy, and stereotactic radiosurgery are three modern radiotherapy applications that commonly use dosimetry of small fields. Field sizes ranging from 1 × 1 cm² to 5 × 5 cm² are taken for analysis. Varian Clinac IX SN6298 was utilized for both 6 and 12 MeV electron beams, using the TRS-398 and IAEA Technical Reports Series No. 483 procedure as the standard. The beam profile and the percentage of depth dosage (PDD) were finally ascertained in a water phantom. Various percent dosages and Bremsstrahlung tail regions were experimentally measured from the PDD curves. With an increase in field size (s), R100, R90, R80, R50, and Rp all rose for the medical linear accelerators. In the CC13 chamber, this held true for both 6 MeV and 12 MeV electron beams. The area of the bremsstrahlung tail grows as energy increases. This may result in modifications to the penumbra region's dosage distribution. Beam profiles revealed that dose was scattered more in small fields than in intermediate sizes. The interactions between the radiation beam, detector, and surrounding materials make small-field dosimetry difficult. Additionally, none of the beam symmetries exceed 2%. Bangladesh J. Nuclear Med. 28(1): 135-141, 2025